Subsidies, Trade, and International Cooperation. (International Monetary Fund, 2022)
The international organizations (IOs) authoring this report can strengthen their individual and joint work to support governments in this endeavor. While the brunt of this work lies with finance ministries, trade ministries, and sectoral and specialized agencies of national governments, international organizations have key roles to play. The four authoring institutions are examining ways to help, individually and jointly, such as by collecting, organizing, and sharing data, coordinating analytical work agendas to develop methodologies to assess the cross-border effects of different forms of subsidies, and supporting inter-governmental dialogues. This will involve reaching out to and working with other international institutions as well.